Altered cerebellar-cortical resting-state functional connectivity in cannabis users. (July 2021) - Schnakenberg Martin, Ashley M; Kim, Dae-Jin; Newman, Sharlene D; Cheng, Hu; Hetrick, William P; Mackie, Ken; O'Donnell, Brian F
Background: Cannabis use has been associated with abnormalities in cerebellar mediated motor and non-motor (i.e. cognition and personality) phenomena. Since the cerebellum is a region with high cannabinoid type 1 receptor density, these impairments may reflect alterations of signaling between the cerebellum and other brain regions. Aims: We hypothesized that cerebellar-cortical resting-state functional connectivity (rsFC) would be altered in cannabis users, relative to their non-using peers. It was also hypothesized that differences in rsFC would be associated with cannabis use features, such as age of initiation and lifetime use. Methods: Cerebellar-cortical and subcortical rsFCs were computed between 28 cerebellar lobules, defined by a spatially unbiased atlas template of the cerebellum, and individual voxels in the cerebral regions, in 41 regular cannabis users (20 female) and healthy non-using peers ( N = 31; 18 female). We also investigated associations between rsFC and cannabis use features (e.g. lifetime cannabis use and age of initiation). Results: Cannabis users demonstrated hyperconnectivity between the anterior cerebellar regions (i.e. lobule I-IV) with the posterior cingulate cortex, and hypoconnectivity between the rest of the cerebellum (i.e. Crus I and II, lobule VIIb, VIIIa, VIIIb, IX, and X) and the cortex. No associations were observed between features of cannabis use and rsFC. Conclusions: Cannabis use was associated with altered patterns of rsFC from the cerebellum to the cerebral cortex which may have a downstream impact on behavior and cognition.